2014
DOI: 10.1177/0333102414552533
|View full text |Cite
|
Sign up to set email alerts
|

Medication-overuse headache in China: Clinical profile, and an evaluation of the ICHD-3 beta diagnostic criteria

Abstract: MOH in China is associated with lower educational level and annual income. MOH has rarely been diagnosed and correctly treated in China. ICHD-3 beta appears to be more appropriate for the diagnosis of MOH than previous versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
21
1
1
Order By: Relevance
“…And MOH accounted for approximately 60% of CDH. Our group's another study [26] showed MOH clinical profile -MOH in China was associated with lower educational level and annual income. A recent report [27] also suggested MOH was more common in the less well educated.…”
Section: Discussionmentioning
confidence: 81%
“…And MOH accounted for approximately 60% of CDH. Our group's another study [26] showed MOH clinical profile -MOH in China was associated with lower educational level and annual income. A recent report [27] also suggested MOH was more common in the less well educated.…”
Section: Discussionmentioning
confidence: 81%
“…There is no large-scale epidemiological data on MOH in China. Dong [ 5 ] retrospectively analyzed the clinical features of 240 patients with MOH and discovered only two patients (0.8 %) had previously been given the diagnosis of MOH. Furthermore, the median time to diagnosis after the estimated onset of the disorder was 4.0 years.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A number of acute headache treatments may cause MOH, 7 and the medications that are predominantly associated with MOH vary from country to country. 1,7,9,10 Opioids such as codeine are particularly problematic, as they are consistently associated with increasingly severe headaches 11 ( Table 12 ) and poor outcomes after withdrawal. 13 In a number of regions, including Hong Kong and Japan, codeine-containing medication is only available by prescription.…”
Section: Medication Overuse Headache: Strategies For Prevention and Tmentioning
confidence: 99%